Factors influencing consumer potato storability in the warm tropics - Tupac Yupanqui, Alberto L., author; Knutson, Kenneth W., advisor; Harrison, Monty D., committee member; Cranshaw, Whitney S., committee member (Colorado State University. Libraries, 1990)
This study was done to determine the feasibility of and explore ways to store consumer potatoes in the warm tropics and reduce storage losses to acceptable levels. The research was done during 2 years, 1988 and 1989, at the mid-elevation jungle research station of the International Potato Center located at San Ramon (800 m elevation), Peru. Pathogen induced rotting is the major cause of loss during storage in the warm tropics. Studies were done to evaluate the storage potential of clones adapted to the warm tropics and determine if any significant relationship existed between storage potential and rotting response to Erwinia and Fusarium spp. when inoculated separately and simultaneously. Finding a suitable relationship would simplify screening in breeding programs to identify progeny with good storage potential. Some of the more suitable clones that were identified for storage in the warm tropics were Desiree, Kufri Jyoti, Serrana, LT-5 and B71 240.2. A significant relationship between storage potential and rotting induced by inoculation was only obtained when the Erwinia and Fusarium spp. were inoculated simultaneously. Since rapid wound healing is essential to reduce pathogen invasion and rotting, the rapidity of wound healing was evaluated. Thirteen of 15 test clones showed over a 90% reduction in F. solani induced dry rot after only 6 days at 25 C. Thus, this evaluation is probably not sufficiently sensitive to differentiate clones in their storage potential. Delaying harvest for 8 days after vine senescence to allow skin setting was slightly beneficial during the dry season but was detrimental during the wet season. A hazard of delaying harvest is the possibility of increased potato tuber moth (PTM) infestation. Removing visibly diseased, insect infested and damaged tubers before storage was very effective in reducing storage losses due to rotting and PTM infestation. Dipping potatoes in solutions of sodium hypochlorite and thiabendazole was very detrimental. However, dusting with thiabendazole just after harvest and dusting with chloro-isopropyl-phenyl-carbamate (CIPC) after 4 weeks was beneficial. CIPC did not reduced sprouting but completely controlled PTM infestation. This research has shown that it is possible to store potatoes in the warm tropics using the proper clones and procedures.
Covers not scanned.
Keywords: Potatoes -- Storage -- Tropics; Potatoes -- Handling -- Tropics